Efficacy of Manufacturer Recommended Microwave Time Against Listeria monocytogenes in Ready-to-Eat Chicken Products - Morey, A.; Singh , M.; McKee, S.R. (International Journal of Poultry Science, 2012)
This study evaluated the effect of manufacturer-recommended microwave times on Listeria monocytogenes in Ready-to-Eat (RTE) poultry products. Three chicken products including battered and breaded chicken patties, fully cooked chicken breast fillets (both frozen) and chicken sausages (refrigerated) were inoculated with streptomycin-resistant (1500 μg/ml) L. monocytogenes (Brie 1) at low (ca. ~4 log10 CFU/ml) and high (ca. ~9 log10 CFU /ml) levels. Following 12 h of either frozen or refrigerated storage, random samples (n = 3 of each product) were individually microwaved for recommended time, undercooked and overcooked. Survival of L. monocytogenes after microwaving was determined by spread plating the samples and enumerating bacterial colonies on BHIA+streptomycin (1500 μg/ml). Analysis of variance with Duncans’ grouping was conducted to determine significant differences in survival (α = 0.05). Microwaving the chicken patties inoculated with high levels of bacteria for a recommended time of 1 min increased surface temperature to 64°C-74°C leading to approximately 1-log reduction (p